IN VITRO ANTI-PLATELET AGGREGATION ACTIVITY OF HYDROXYPROPYL CELLULOSE–CYSTEAMINE BASED NANOPARTICLES CONTAINING CRUDE BROMELAIN - RAHMAT, DENI; NURHIDAYATI, LILIEK; MARCELLA, MARCELLA; SUMARNY, ROS; LAKSMITAWATI, DIAN RATIH (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the present study was to formulate bromelain into nanoparticles in order to improve its stability and activity. Methods: Crude bromelain was prepared by protein precipitation from the pineapple stem juice using ammonium sulphate at the concentration of 60% (w/v). Nanoparticles containing crude bromelain were generated using the ionic gelation method with hydroxypropyl cellulose–cysteamine (HPC-cysteamine) conjugate as a matrix. Crude bromelain was then added to the HPC-cysteamine solution for ionic interaction to construct the nanoparticles, which were then analyzed for their particle size and zeta potential. The resulting nanoparticles were mixed with adenosine diphosphate (ADP) to perform anti-platelet aggregation. Results: The nanoparticle had 928.3 nm in particle size and-7.25 mV in zeta potential. Anti-platelet activity of crude bromelain and the nanoparticles were determined with modification of light transmission aggregometry (LTA), in which ADP was used to induce an aggregation while a spectrophotometer UV-Vis was used to measure the absorbance at the wavelength of 600 nm. The result showed that crude bromelain and the nanoparticles rendered percentage inhibition of 8.00±1.17% and 48.56±11.19%, respectively. Conclusion: Based on the result of a one-way analysis of variance (ANOVA), it was concluded that there was a significant difference in percentage inhibition between the two samples. The nanoparticles demonstrated a better anti-platelet aggregation activity compared to crude bromelain.